Social Construction of Women Leaders among College Students - A. Octamaya Tenri Awaru; Muhammad Syukur; Muhammad Taufik Hidayat; Supriadi Torro (International Journal of Qualitative Research, 2021)
Over the years men have been dominant as leaders and consider women less suitable and competent for leadership roles due to various reasons. On the contrary women of the twentieth and twenty-first centuries are emerging as successful leaders in various segments of society. But with enormous struggle and they are also few in number compared to men. Gender stereotyping is no more a relevant concept as men and women occupy all positions irrespective of their gender. Leadership has been possible for some women while others don’t get the same opportunity men get in leading organizations. Some women struggle and fight their way into leadership positions while others don’t. Women are ignored or set aside based on several reasons one primary being they need to take care of the home. Though all sort of justification is made for women not being in leadership positions it is important to understand the loss the society faces due to minimum women leaders. Despite all of this, women are said to have equal rights with men in terms of leadership. This study examines the factors that help in the formation of women leaders among the students and the social construction of women leaders among the students. This study uses a qualitative method via a structured interview. The informants of this study are selected based on certain criteria with the belief that the informants will provide accurate information related to women’s leadership among students.